Understanding the interactions between iron supplementation, infectious disease and adverse birth outcomes is essential to guide public health recommendations - Freya J. I. Fowkes; Eliza Davidson; Paul A. Agius; James G. Beeson (BMC Medicine, 2019)
Abstract Pregnant women are highly susceptible to anaemia and iron deficiency due to the increased demands of pregnancy as well as other factors. Iron supplementation is recommended in pregnancy, yet the benefits on newborn outcomes are variable between populations, most likely due to the heterogeneity in the prevalence of iron deficiency, detrimental birth outcomes and infectious diseases. Furthermore, there are concerns regarding iron supplementation in malaria-endemic areas due to reports of increased risk of malaria in those receiving iron. This is compounded by limited knowledge of how iron deficiency, anaemia, malaria, and other infections may interact to influence birth outcomes. In a recent cohort study in Papua New Guinea, where there is a high burden of infections and iron deficiency, we found that iron deficiency in pregnancy was associated with a reduced risk of adverse birth outcomes. However, this effect could not be wholly explained by interactions between iron deficiency and malaria. We proposed that iron deficiency may confer a degree of protection against other infectious pathogens, which in turn caused improvements in birthweight. We argue that further studies in multiple populations are crucial to elucidate interactions between iron status, iron supplementation and birthweight as well as to understand the context-specific benefits of iron supplementation in pregnancy and inform public policy. Focus should be given to haematological studies on anaemia, haemodilution and iron absorption, as well as investigating infectious diseases and other nutritional deficiencies. This is a particular priority in resource-constrained settings where the prevalence of iron deficiency, poor nutrition, infections and poor birth outcomes are high. While current recommendations of iron supplementation and malaria prophylaxis to reduce the burden of poor pregnancy outcomes should be supported, the strength of evidence underpinning these must be improved and new insights should be garnered in order to maximise improvements in maternal and child health. Please see related article: https://bmcmedicine.biomedcentral.com/articles/10.1186/s12916-018-1146-z . Please see related article: https://bmcmedicine.biomedcentral.com/articles/10.1186/s12916-019-1375-9 .